DRINKING WATER TREATMENT PLANTS MANAGEMENT COOPERATION: KEY LEGAL ASPECTS TO MEET COMMUNITY NEEDS - Siregar, Mahmul; Sukarja, Detania (Universitas Syiah Kuala, 2023)
Water Treatment Plant (WTP)companies experience dilemma between the obligation to provide healthy drinking water and the company's limitations in providing water infrastructure. This encourages state water companies to collaborate with the private sector to procure infrastructure. This study raises issues related to the concept of state control over water and its implications for cooperation schemes for drinking water supply, as well as the legal aspects of cooperation in the management of drinking water treatment plants. This study uses normative research method with statute and conceptual approach. The result shows that considering the status of state water companies are subject to public finance accountability, that parties must design and implement the cooperation with due care, that is the principles of good corporate governance. This principle remains difficult to implement as many challenges facing. Hence the more efforts and cooperation with associated stakeholders should be taken into account.